2016
DOI: 10.3390/md14050101
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic Approaches towards Deciphering Glycolipids from Microalgae as a Reservoir of Bioactive Lipids

Abstract: In recent years, noteworthy research has been performed around lipids from microalgae. Among lipids, glycolipids (GLs) are quite abundant in microalgae and are considered an important source of fatty acids (FAs). GLs are rich in 16- and 18-carbon saturated and unsaturated fatty acids and often contain polyunsaturated fatty acids (PUFAs) like n-3 α-linolenic (ALA 18:3), eicosapentaenoic (EPA, 20:5) and docosahexaenoic (DHA, 22:6). GLs comprise three major classes: monogalactosyldiacyl glycerolipids (MGDGs), dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 109 publications
(347 reference statements)
1
81
0
3
Order By: Relevance
“…b (d'ippolito et al, 2015). c (Yongmanitchai and Ward, 1992;Plouguerné et al, 2014;d'ippolito et al, 2015;da Costa et al, 2016). d (Volkman et al, 1998;Viegelmann et al, 2014).…”
Section: Lipids and Fatty Acids In Diatomsunclassified
“…b (d'ippolito et al, 2015). c (Yongmanitchai and Ward, 1992;Plouguerné et al, 2014;d'ippolito et al, 2015;da Costa et al, 2016). d (Volkman et al, 1998;Viegelmann et al, 2014).…”
Section: Lipids and Fatty Acids In Diatomsunclassified
“…Polar lipids are nowadays recognized as an important reservoir of fatty acids with nutritional value, e.g., n -3 FAs [5,6], and they are also considered high-value novel lipids with beneficial health effects such as antitumoral [7,8], antiviral [8,9], antifungal [10], antibacterial [11], and anti-inflammatory [11,12], with potential applications in the nutraceutical and pharmaceutical industries [7,8,11]. However, in spite of their recognized potential, they are still scarcely studied [12,13,14,15]. Some studies reported that polar lipids isolated from seaweeds can promote growth-inhibiting effects on human hepatocellular carcinoma cell lines (HepG2) [16] and thus can act as inhibitors of DNA polymerases with capability to inhibit tumor cell proliferation [17].…”
Section: Introductionmentioning
confidence: 99%
“…To fully explore the bioactive properties of seaweed lipids and thus contribute to seaweed valorization, it is fundamental to characterize their structure and understand how it modulates bioactivity [13,14]. Nowadays, the detailed structural characterization of lipids can be accomplished by using mass spectrometry (MS) coupled with liquid chromatography (LC).…”
Section: Introductionmentioning
confidence: 99%
“…Such pigments exhibit colours from green, yellow, brown or red. Production of microalgal pigments may significantly vary dependent on many factors such as temperature, irradiation intensity, photoperiods, colour absorption wavelength, pH, nutrient limitation, nitrogen supplements, salinity, presence of pesticides or heavy metals [30]. Table 4 presents the reference data related to the extraction, isolation and characterization of some isoprenoids, especially pigments Table 4.…”
Section: Bioactive Metabolites Found In Microalgae Speciesmentioning
confidence: 99%
“…technique ro screen the protein fingerprint and characterize the phenotype (genus, species), and in some cases, the strains also of microalgae, comparing the spectra of unknown microorganisms to reference spectra found in international databases [55].The possibility of using MALDI-TOF-MS for the rapid identification of pathogenic and non-pathogenic species of the genus Prototheca has been recently demonstrated [30]. This provides reproductible and unique spectra covering a wide m/z range (2000-20 000 Da) for each of the strains used in the present study.…”
Section: Matrix Assisted Laser Desorption Ionization Time-of-flight Mmentioning
confidence: 99%